2000
DOI: 10.1046/j.1525-1497.2000.91119.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication breakdown in the outpatient referral process

Abstract: OBJECTIVE:To evaluate primary care and specialist physicians' satisfaction with interphysician communication and to identify the major problems in the current referral process. DESIGN:Surveys were mailed to providers to determine satisfaction with the referral process; then patient-specific surveys were e-mailed to this group to obtain real-time referral information. SETTING: Academic tertiary care medical center.PARTICIPANTS: Attending-level primary care physicians (PCPs) and specialists. MEASUREMENTS AND MAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
259
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(269 citation statements)
references
References 12 publications
5
259
0
5
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] Studies have found high rates of dissatisfaction with different aspects of primary-specialty communication-and specifically referral communication. 4,5 This problem is of increasing concern, as there have been recent national trends towards proportionally more primary care visits resulting in referrals to specialty care. 11 Optimal communication between primary and specialty providers is essential for realizing the goals of the patient-centered medical home (PCMH) care model, an increasingly dominant paradigm in primary care throughout the country.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Studies have found high rates of dissatisfaction with different aspects of primary-specialty communication-and specifically referral communication. 4,5 This problem is of increasing concern, as there have been recent national trends towards proportionally more primary care visits resulting in referrals to specialty care. 11 Optimal communication between primary and specialty providers is essential for realizing the goals of the patient-centered medical home (PCMH) care model, an increasingly dominant paradigm in primary care throughout the country.…”
Section: Introductionmentioning
confidence: 99%
“…45 Studies have shown increased physician satisfaction and better feedback from specialists when referral templates are used to standardize referral communication. 43,46,47 For instance, capturing the reason for consult is a key but often omitted step in the referral process, 13,[48][49][50][51] and thus electronic referrals must be designed to include a clearly defined justification of the referral. Furthermore, communicating details related to urgency is an important component of referral content.…”
Section: Teaching Point 2: Evaluation Must Determine Whether Technolomentioning
confidence: 99%
“…10,11 At our institution, Brigham and Women's Hospital (BWH), the specialty referral process was problematic as well, with 63 % of PCPs indicating dissatisfaction with the procedures that were in place. 13 Long wait times for new visits to many specialties forced BWH PCPs to refer to non-BWH specialists. These non-BWH specialty visits increase fragmentation of care and hinder coordination of specialty care for our primary care population.…”
Section: Introductionmentioning
confidence: 99%
“…While the primary onus of critical results communication in radiology has largely been placed on the interpreting radiologist, many communication failures are the result of lack of clinician availability or follow-up [4,22]. Current critical results communication models often rely on manual communication attempts to ensure that the critical results are successfully communicated, with frequent outsourcing of responsibilities to third parties.…”
Section: Innovation Opportunitymentioning
confidence: 99%